2019
DOI: 10.9778/cmajo.20190040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic kidney disease and cardiovascular comorbidities in adults in First Nations communities in northwest Ontario: a retrospective observational study

Abstract: Background: The prevalence of adult chronic kidney disease and cardiovascular comorbidities in Canadian Indigenous communities is largely unknown. We conducted a study to document the prevalence of chronic kidney disease and concurrent diabetes mellitus, hypertension and dyslipidemia in a First Nations population in northwest Ontario. Methods: In this observational study, we used retrospective data collected from regional electronic medical records of 16 170 adults (age ≥ 18 yr) from 26 First Nations communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…However, high burden of chronic diseases and immunocompromising conditions, along with unfavourable socioeconomic conditions, are important factors predisposing Indigenous people to invasive bacterial disease [ 40 , 72 ]. As Indigenous Canadians have high burden of obesity, diabetes, circulatory diseases, chronic kidney disease, and cancer, this suggests that an increased IPD rate in Indigenous adults is due to the increased prevalence of risk factors rather than lack of anti-capsular antibodies [ 73 , 74 ]. Indeed, according to our recent data, among northwestern Ontario adults with IPD, prevalence of immunocompromising conditions was much higher in Indigenous than in non-Indigenous patients (66% vs. 29.5%, p < 0.001) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, high burden of chronic diseases and immunocompromising conditions, along with unfavourable socioeconomic conditions, are important factors predisposing Indigenous people to invasive bacterial disease [ 40 , 72 ]. As Indigenous Canadians have high burden of obesity, diabetes, circulatory diseases, chronic kidney disease, and cancer, this suggests that an increased IPD rate in Indigenous adults is due to the increased prevalence of risk factors rather than lack of anti-capsular antibodies [ 73 , 74 ]. Indeed, according to our recent data, among northwestern Ontario adults with IPD, prevalence of immunocompromising conditions was much higher in Indigenous than in non-Indigenous patients (66% vs. 29.5%, p < 0.001) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, metabolic syndrome in childhood in an Australian Aboriginal population was associated with subclinical atherosclerosis in 19-year-olds, possibly mediated by increased inflammation [56]. Canadian First Nations populations show an increased incidence of obesity [57] and chronic kidney disease and associated cardiovascular comorbidities [58]. The Canadian government has provided a food subsidy to bring perishable fruits and vegetables to remote rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…We identified one study on the prevalence of chronic kidney disease in Northwestern Ontario among 26 remote First Nations communities. The study identified a 7% prevalence rate of stage 3-5 chronic kidney disease, double the rate of the general Canadian population [19].…”
Section: Discussionmentioning
confidence: 99%
“…Ontario First Nations communities are disproportionally affected by chronic kidney disease, with a prevalence of stage 3-5 disease double that of the general population; however, direct comparisons of clinical characteristics between Indigenous and non-Indigenous patients have not been conducted in these studies [19]. Our study objective was to directly compare demographic and clinical characteristics of Indigenous and non-Indigenous adults with ESKD receiving dialysis through the TBRHSC over the past 5 years.…”
Section: Recent Studies Have Found That Adults Living In Northwesternmentioning
confidence: 99%